2015
DOI: 10.1016/j.coph.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

PI3K inhibitors in inflammation, autoimmunity and cancer

Abstract: The healthy immune system protects against infection and malignant transformation without causing significant damage to host tissues. Immune dysregulation results in diverse pathologies including autoimmune disease, chronic inflammatory disorders, allergies as well as immune deficiencies and cancer. Phosphoinositide 3-kinase (PI3K) signalling has been shown to be a key pathway in the regulation of the immune response and continues to be the focus of intense research. In recent years we have gained detailed und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
192
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(194 citation statements)
references
References 80 publications
(107 reference statements)
2
192
0
Order By: Relevance
“…The PI3K–protein kinase B (PI3K–Akt) pathway regulates the size, survival, angiogenesis, and inflammation of cardiomyocytes 32. PI3K signalling can promote proinflammatory cytokine production by activating nuclear factor‐κB (NFκB) downstream of AKT and can mediate IL‐6 expression, which, in our study, was down‐regulated by microcurrent 33. TGF‐β plays a central role in the induction of fibrosis by stimulation of the Smad system, which in turn increases the expression of collagen types I, III, and VI and accelerates the production of extracellular matrix proteins 31.…”
Section: Discussionmentioning
confidence: 61%
“…The PI3K–protein kinase B (PI3K–Akt) pathway regulates the size, survival, angiogenesis, and inflammation of cardiomyocytes 32. PI3K signalling can promote proinflammatory cytokine production by activating nuclear factor‐κB (NFκB) downstream of AKT and can mediate IL‐6 expression, which, in our study, was down‐regulated by microcurrent 33. TGF‐β plays a central role in the induction of fibrosis by stimulation of the Smad system, which in turn increases the expression of collagen types I, III, and VI and accelerates the production of extracellular matrix proteins 31.…”
Section: Discussionmentioning
confidence: 61%
“…Importantly, class IA PI3K isoforms (PI3Ka, b, d) are adapted to regulation by receptors signal through protein tyrosin kinases, whereas class IB PI3K (PI3Kg) is adapted to regulation by GPCRs via direct binding to Gbg subunits. [26][27][28][29] Tim-3 expression, in response to certain cytokines, has been reported to be induced by activation of the PI3K pathway. 26 We previously showed that pS6 is decreased in TIL after PD-1 stimulation, 30 potentially linking PD-1 to the PI3K-Akt-mTOR pathway.…”
Section: Tim-3 Upregulation Upon Pd-1 Blockade Requires Activation Ofmentioning
confidence: 99%
“…[26][27][28][29] Tim-3 expression, in response to certain cytokines, has been reported to be induced by activation of the PI3K pathway. 26 We previously showed that pS6 is decreased in TIL after PD-1 stimulation, 30 potentially linking PD-1 to the PI3K-Akt-mTOR pathway. Since TCR/CD28 co-stimulation leads to PI3K/Akt activation, and PD-1 ligation causes inhibition of TCR proximal signaling through SHP-2 27 , leading to decreased PI3K activity, we hypothesized that Tim-3 upregulation after PD-1 blockade might be caused by increased PI3K activity due to de-repression by PD-1 blockade.…”
Section: Tim-3 Upregulation Upon Pd-1 Blockade Requires Activation Ofmentioning
confidence: 99%
“…Hence, manipulation of the PI3K pathway represents an interesting approach for treatment of a number of different pathological conditions such as cancer, where inhibitors of class IA PI3K with varying isoform selectivity profiles have already been established as treatment options for different indications. 1 In the immune system, the PI3K delta isoform plays a central role in both innate and adaptive immune cell functions. Taking advantage of the strong dependency of B cells on functional PI3Kδ, 2 the oral PI3Kδ inhibitor Idelalisib has been successfully developed as a novel treatment for different types of B-cell malignancies.…”
mentioning
confidence: 99%